1982
DOI: 10.1002/bbpc.198200058
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Illumination on the Flat Band Potential of the Contact TiO2/CH3CN(+ H2O)

Abstract: Results are reported on the flat band potential Vfb of the contact TiO2/CH3CN. The informations were taken from capacitance/voltage and photocurrent/voltage measurements. As electrolyte either pre‐dried CH3CN or various mixtures of dried CH3CN with H2O were used. It was found that both the addition of H2O and illumination with band gap light affect Vfb considerably. – It could be shown that Vfb‐values determined from photocurrent/potential measurements differ up to 2 V from values evaluated from capacitance/po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…The values are in line with the values reported by Redmond and Fitzmaurice and our previous results which are determined from Mott–Schottky analysis . We note that our value of E fb in dry CH 3 CN (−2.10 V) is comparable to those obtained by Schumacher , and Fitzmaurice . These potentials are significantly more negative than those reported for CH 3 CN in other literature studies. ,, If we take this value as E fb of the hybrid, the endergonic electron injection from ZnP into dry TiO 2 particles would be much slower.…”
Section: Resultssupporting
confidence: 92%
“…The values are in line with the values reported by Redmond and Fitzmaurice and our previous results which are determined from Mott–Schottky analysis . We note that our value of E fb in dry CH 3 CN (−2.10 V) is comparable to those obtained by Schumacher , and Fitzmaurice . These potentials are significantly more negative than those reported for CH 3 CN in other literature studies. ,, If we take this value as E fb of the hybrid, the endergonic electron injection from ZnP into dry TiO 2 particles would be much slower.…”
Section: Resultssupporting
confidence: 92%
“…−2 V) and after illumination (ca. 0 V vs NHE) of E fb of TiO 2 for single crystals vary in +2 V, , and there is a difference between the E fb from the photocurrent (−0.6 V) and Mott−Schottky methods (<−1 V); this could be due to the photo-oxidation of the electrolyte or traces of water that modified the liquid/TiO 2 interface or relaxation phenomena caused by surface states or traps that affect the impedance measurements . Redmond and Fitzmaurice found that Li + could change the E fb from −1.8 V, without Li + , to −0.6 V vs NHE with Li + ≥ 0.01 M .…”
Section: Resultsmentioning
confidence: 99%
“…In the present systems, we assumed that or is the main oxidizing species, as given by eq 7, where has a flat band potential for the valence band ( E VB ) of about +2.1 V vs NHE …”
Section: Resultsmentioning
confidence: 99%